2019
DOI: 10.1017/s0142716419000018
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the complexity of the relations of metalinguistic skills to word reading with struggling adult readers: Shared, independent, and interactive effects

Abstract: This study investigates the shared, independent, and interactive effects of metalinguistic skills (phonological awareness, morphological awareness, and orthographic knowledge) to word reading with a sample of struggling adult readers. Controlling for vocabulary knowledge, a second-order latent factor of metalinguistic awareness accounted for unique variance (62.5%) in adults’ word reading skills. Two-way latent interactions between the metalinguistic skills (phonological awareness × morphological awareness, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
(175 reference statements)
0
1
0
Order By: Relevance
“…Recognized theoretical frameworks of literacy emphasize that awareness of morphemes and processing morphological information in text supports reading comprehension and other literacy skills, including word reading and vocabulary (Levesque et al, 2021;Perfetti & Stafura, 2014). Moreover, research with adult education learners has found that morphological knowledge is related to better word reading (Tighe et al, 2019), vocabulary (Fracasso et al, 2016), and reading comprehension skills (Tighe & Schatschneider, 2016a, b). Morphological knowledge can help adult education learners because morphemes enhance multiple reading skills (Kirby & Bowers, 2017).…”
Section: Why Is Morphological Knowledge Important To Literacy?mentioning
confidence: 99%
“…Recognized theoretical frameworks of literacy emphasize that awareness of morphemes and processing morphological information in text supports reading comprehension and other literacy skills, including word reading and vocabulary (Levesque et al, 2021;Perfetti & Stafura, 2014). Moreover, research with adult education learners has found that morphological knowledge is related to better word reading (Tighe et al, 2019), vocabulary (Fracasso et al, 2016), and reading comprehension skills (Tighe & Schatschneider, 2016a, b). Morphological knowledge can help adult education learners because morphemes enhance multiple reading skills (Kirby & Bowers, 2017).…”
Section: Why Is Morphological Knowledge Important To Literacy?mentioning
confidence: 99%